Managing Conflict at Sea: The Case of Norway and Russia in the Svalbard Zone - Andreas Østhagen (Arctic Review on Law and Politics, 2018)
In 1977, Norway established a maritime Fisheries Protection Zone (FPZ) around Svalbard, yet avoided claiming an outright Exclusive Economic Zone (EEZ). A dispute with Russia over the status of the Zone arose. In the late 1990s, Norwegian enforcement of fisheries regulations became stricter, as fish stocks were in decline. This led the Norwegian Coast Guard to attempt to arrest Russian fishing vessels on several occasions, resulting in reactions from Russian fishermen, as well as officials in Murmansk and Moscow. In 1998, 2001, 2005, and 2011 specifically, incidents had the potential to escalate beyond a fisheries issue. Today, an event in the maritime zone is of concern to both Norwegian and Russian authorities. Given the potential volatility of events in the FPZ, how do Norway and Russia manage to avoid escalation in the case of a crisis? Whereas previous scholarly work has explicitly focused on the legal status of Svalbard and its maritime zones, or looked at how Norway manages fisheries in cooperation with Russia, this article brings forth new knowledge by examining the specific incidents in the Zone and placing these in the wider context of conflict theory. Limited to the Norwegian perceptions of the dispute only, this article adds to our understanding of this specific issue of Arctic conflict management and governance. Based on several years of data collection through interviews, the argument put forth is that Norwegian and Russian cooperation is based on both mutual interests and the socializing effects of cooperative mechanisms, which in turn are key to avoid escalation in crisis-scenarios. In sum, we need to recognise how a combination of economic interests and the effects of socialisation have enabled Norway and Russia to keep conflict levels low, when incidents at sea have occurred.